ENHANCED DEPTH IMAGING OPTICAL COHERENCE TOMOGRAPHY FEATURES IN AREAS OF CHORIOCAPILLARIS HYPOPERFUSION. Issue 10 (October 2016) - Invernizzi, Alessandro; Agarwal, Aniruddha; Cozzi, Mariano; Viola, Francesco; Nguyen, Quan Dong; Staurenghi, Giovanni
Abstract : Purpose: To detect choriocapillaris changes by enhanced depth imaging optical coherence tomography (EDI-OCT) in areas of choriocapillaris hypoperfusion visualized on indocyanine green angiography. Methods: Combined indocyanine green angiography and EDI-OCT from patients diagnosed with inflammatory choriocapillaris hypoperfusion were retrospectively analyzed. The EDI-OCTs were compared with indocyanine green angiography to detect choriocapillaris changes suggestive of choriocapillaris hypoperfusion in both active stage (AS) and inactive stage of the disease. The EDI-OCT was graded by two independent observers for choriocapillaris pattern (normal/altered) and reflectivity (hyper/hypo/isoreflective) changes. Manual measurements of choriocapillaris thickness were obtained. Interobserver agreement was assessed using Cohen's kappa, and differences in groups were assessed using McNemar's test. Results: Forty-two lesions from 11 eyes (8 patients, 3 males) were analyzed. Three patients (4 eyes, 17 lesions) were diagnosed with serpiginous choroiditis, and 5 patients (7 eyes, 25 lesions) were diagnosed with acute posterior multifocal placoid pigmented epitheliopathy. All the lesions demonstrated choriocapillaris hyporeflectivity on EDI-OCT during AS and isoreflectivity during inactive stage. The characteristic choriocapillaris dotted pattern was absent during AS. Choriocapillaris thickness at the sites of hypoperfusion was significantly higher during AS (63.07 ± 16.47 μ m) than in inactive stage (22.92 ± 7.65 μ m) ( P < 0.001). Disruption of retinal pigment epithelium during AS was strongly associated with choriocapillaris atrophy during follow-up ( P < 0.001). Conclusion: The EDI-OCT shows characteristic choriocapillaris changes suggestive of choriocapillaris hypoperfusion that correlate with ischemia on indocyanine green angiography during both AS and inactive stage of the disease. Abstract : Enhanced depth imaging optical coherence tomography features related to choriocapillaris hypoperfusion as detected by indocyanine green angiography are described. Enhanced depth imaging optical coherence tomography can be considered as a useful noninvasive investigation to evaluate and follow-up patients affected by diseases causing choriocapillaris hypoperfusion, such as serpiginous choroiditis and acute posterior multifocal placoid pigmented epitheliopathy.